2013
DOI: 10.1093/brain/awt105
|View full text |Cite
|
Sign up to set email alerts
|

Memory reorganization following anterior temporal lobe resection: a longitudinal functional MRI study

Abstract: Anterior temporal lobe resection controls seizures in 50–60% of patients with intractable temporal lobe epilepsy but may impair memory function, typically verbal memory following left, and visual memory following right anterior temporal lobe resection. Functional reorganization can occur within the ipsilateral and contralateral hemispheres. We investigated the reorganization of memory function in patients with temporal lobe epilepsy before and after left or right anterior temporal lobe resection and the effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 47 publications
8
79
0
7
Order By: Relevance
“…There is an ongoing debate about the ability of postoperative compensation for verbal memory decline after surgery of the posterior parts of the ipsilateral hippocampus versus contralateral temporomesial structures [37]. We found a relevant fMRI memory-related cortical area within the posterior parahippocampal gyrus, which influenced the postoperative memory outcome more positively when preserved than small hippocampal resection (fig.…”
Section: Discussionmentioning
confidence: 76%
“…There is an ongoing debate about the ability of postoperative compensation for verbal memory decline after surgery of the posterior parts of the ipsilateral hippocampus versus contralateral temporomesial structures [37]. We found a relevant fMRI memory-related cortical area within the posterior parahippocampal gyrus, which influenced the postoperative memory outcome more positively when preserved than small hippocampal resection (fig.…”
Section: Discussionmentioning
confidence: 76%
“…2). 78 Others have suggested that postoperative visual and verbal memory performance is positively associated with the activation of contralateral medial temporal lobe and its connectivity to posterior cingulate cortex ipsilateral to the sclerosed hippocampus after temporal lobe resection. 85 …”
Section: Postoperative Findingsmentioning
confidence: 99%
“…In addition, one study reported that increased activation in the posterior MTL following anterior temporal lobe resection in patients with left mTLE was actually correlated with worse postoperative verbal memory performance. 51 The question of whether "more is better" in terms of activation magnitude is discussed again later.…”
Section: Memory In Temporal Lobe Epilepsy: Activation Tasks and Corrementioning
confidence: 99%
“…Using the probability of clinically meaningful postoperative decline in mTLE as an example, would 3 activated voxels present no risk whereas 15 would signify a strong risk? Although few studies have attempted to quantify this, Bonelli and colleagues 51 reported that activation of the MTL alone showed poor PPV (20%-30%, depending on hemisphere), but also that it did significantly contribute to strong prediction when language lateralization and preoperative test performance were included in the models (PPV 70% for left mTLE/verbal memory change and 100% for right mTLE and visual memory change). Overall, the field is not sufficiently mature to have highly reliable activation tasks or rsFC metrics with appropriate cutoffs for clinical decision making, but this issue is likely years rather than decades away from being resolved.…”
Section: The Added Value Of Fmri In Diagnosis and Predictionmentioning
confidence: 99%